Progress in cryptology -- AFRICACRYPT 2020 : 12th International Conference on Cryptology in Africa, Cairo, Egypt, July 20-22, 2020, Proceedings /: 12th International Conference on Cryptology in Africa, Cairo, Egypt, July 20-22, 2020, Proceedings. (2020) - Unknown
No abstract available